1996
DOI: 10.1007/bf00056293
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence the diversity of saproxylic beetles? A multiscaled study from a spruce forest in southern Norway

Abstract: The diversity in different groups of obligate saproxylic beetles was related to ecological variables at three levels of spatial scale in mature spruce-dominated forest. The variables were connected to: (i) decaying wood, (ii) wood-inhabiting fungi, (iii) the level of disturbance, (iv) landscape ecology, and (v) vegetational structure. Several strong relationships were found at medium (1.kin 2) and large scales (4 kin2), while only weak relationships were found at a small scale (0.16 ha; I ha --104 m2). This ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
3
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(135 citation statements)
references
References 26 publications
6
120
3
5
Order By: Relevance
“…There are contrasting results on the relevance of physical variables as predictors of saproxylic species richness. Positive correlations between the volume of deadwood and saproxylic beetle richness at the plot level have frequently been observed (Grove, 2002, Martikainen et al, McGeoch et al, 2007Similä et al, 2003;Sippola et al, 2002); however several authors found no relationships between the local amount of deadwood and the richness of saproxylic beetle assemblages (Franc et al, 2007;Økland, et al, 1996;Siitonen, 1994;Similä, et al, 2006;). In our study a portion of the variation in species richness was unexplained by our predictive models.…”
Section: "Environmental" Indicatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are contrasting results on the relevance of physical variables as predictors of saproxylic species richness. Positive correlations between the volume of deadwood and saproxylic beetle richness at the plot level have frequently been observed (Grove, 2002, Martikainen et al, McGeoch et al, 2007Similä et al, 2003;Sippola et al, 2002); however several authors found no relationships between the local amount of deadwood and the richness of saproxylic beetle assemblages (Franc et al, 2007;Økland, et al, 1996;Siitonen, 1994;Similä, et al, 2006;). In our study a portion of the variation in species richness was unexplained by our predictive models.…”
Section: "Environmental" Indicatorsmentioning
confidence: 98%
“…The selection of this particular indicator reflects its importance to the 20-25% of forest-dwelling species that are either deadwood dependant or rely on wood-roting fungi, i.e., saproxylic (Elton, 1966;Stokland and Meyeke, 2008). Several studies have shown a significant positive correlation between the amount of deadwood and species richness of saproxylic beetles (Grove, 2002;Jacobs et al, 2007;Martikainen et al, 2000;McGeoch et al, 2007;Økland et al, 1996;Similä et al, 2003;Sippola et al, 2002), wood-inhabiting fungi (Bader et al, 1995;Pentillä et al, 2004;Similä et al, 2006;Stokland et al, 2004), mammals or birds (Mac Nally et al, 2001). Nevertheless, the diversity of deadwood (type, dimension and decay stage) is also an important predictor of saproxylic beetle species richness, as it represents the diversity of possible microhabitats (Ranius and Jonsson, 2007;Siitonen, 2001;Similä et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these microhabitats are lost because they are found in tree species that are not economically desirable, like aspen (Siitonen and Martikainen 1994) and beech (Nilsson and Baranowski 1997). Others are threatened because they are part of trees with large diameters, which are not maintained amid short-lasting even-age stand rotations (Økland et al 1995;Nilsson et al 1995;Siitonen and Saaristo 2000). Th ese and other factors have lead to concern about the diversity of deadwood microhabitats in general, as defi ned by decay states, sizes, and tree species (Økland et al 1995).…”
Section: Alpha Diversitymentioning
confidence: 99%
“…Saproxylic beetles are a functional group of Coleoptera that depend, at some point in their life cycle, on dead or decaying wood or fungi associated with deadwood (Speight 1989;Økland et al 1996). Not only do these insects comprise a large proportion of total forest species richness, but they also play an important role in decomposition and nutrient cycling in forest ecosystems (Siitonen 2001;Grove 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Th ere are few studies of saproxylic invertebrates in eastern Canada compared to many areas of northern Europe (Jonsell et al 1998;Kaila et al 1997;Kolmstrom and Lumatjarvi 2000;Kouki et al 2000;Martikainen 2001;Martikainen and Kouki 2003;Martikainen et al 2000;Muona 1999;Økland et al 1996;Rainius and Jansson 2002;Siitonen 1994Siitonen , 2001Simila et al 2002Simila et al , 2003Sverdrup-Th ygeson and Ims 2002;Vaisanen et al 1993). Only in the last decade have serious investigations of the Nova Scotia saproxylic fauna been undertaken.…”
Section: Introductionmentioning
confidence: 99%